Fines as a Criminal Sanction: Practices and Attitudes of Trial Court Judges in the United States, 1985 - Cole, George F. ([Verlag nicht ermittelbar], 1988)
These data were collected to examine the practices and views of state trial court judges with respect to their use of fines as a criminal sanction. Respondents were asked about the composition of their caseloads, sentencing practices (including fines imposed for various circumstances), available information about the offender at time of sentencing, enforcement and collection procedures in their courts, and their attitudes toward the use of fines. In addition to questions concerning the judges' use of fines and other sanctions, the questionnaire presented the judges with hypothetical cases.